2018
DOI: 10.1002/humu.23408
|View full text |Cite
|
Sign up to set email alerts
|

Very short DNA segments can be detected and handled by the repair machinery during germline chromothriptic chromosome reassembly

Abstract: Analyses at nucleotide resolution reveal unexpected complexity of seemingly simple and balanced chromosomal rearrangements. Chromothripsis is a rare complex aberration involving local shattering of one or more chromosomes and reassembly of the resulting DNA segments. This can influence gene expression and cause abnormal phenotypes. We studied the structure and mechanism of a seemingly balanced de novo complex rearrangement of four chromosomes in a boy with developmental and growth delay. Microarray analysis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…In the studied case, the paternal origin of the CCR allele, the clustering of the majority of breakpoints within a few megabases of nucleotides, and the molecular signature of the breakpoint junctions (i.e., blunt ends, microhomology, and nontemplated insertions) supported a single catastrophic event as the mechanism of formation. Similar to a recent report by Slamova et al (), we observed very small fragments from shattered chromosomes that were apparently captured and incorporated into derivative chromosomes by the repair machinery (Slamova et al, ), providing further support that CNVs can be very short. We conclude that differentiation between CNVs and indels should be defined by the mechanism by which they arise rather than by size alone.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the studied case, the paternal origin of the CCR allele, the clustering of the majority of breakpoints within a few megabases of nucleotides, and the molecular signature of the breakpoint junctions (i.e., blunt ends, microhomology, and nontemplated insertions) supported a single catastrophic event as the mechanism of formation. Similar to a recent report by Slamova et al (), we observed very small fragments from shattered chromosomes that were apparently captured and incorporated into derivative chromosomes by the repair machinery (Slamova et al, ), providing further support that CNVs can be very short. We conclude that differentiation between CNVs and indels should be defined by the mechanism by which they arise rather than by size alone.…”
Section: Discussionsupporting
confidence: 91%
“…Many of the larger insertions at breakpoint junctions were nontemplated insertions; yet, in others, runs of 21–41 nucleotides could be mapped back to the regions of chromosomal shattering, mostly to Chromosome 6 (Tables and S3). Some of these likely represent very short DNA segments that were incorporated into the reassembled chromosomes by the repair machinery (Slamova et al, ). As an example, 41 bp in junctions der5_jct7&8 mapped to the gap between Segments 6–12 and 6–13, and 25 bp at the same junction mapped to the segment between 6–3 and 6–4 (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, case 2, similar to case 1, fits with a chromothripsis-like event leading in the father to an apparently reciprocal translocation involving chromosomes 6 and 14. Sequence analysis on the breakpoints showed less precisely fused break-end with three out of five breakpoints that were shortened by small deletions as frequently observed in translocation formation in mammalian cells (Simsek & Jasin, 2014;Weinstock, Elliott, & Jasin, 2006). The remaining junctions displayed repairbased mechanisms as NHEJ and microhomology-mediated processes.…”
Section: Casementioning
confidence: 83%
“…Several examples of chromothriptic‐like events associated with insertional translocation have been recently reported in cases with multiple CNVs (Gu et al, ; Kato et al, ; Kurtas et al, ). Taking into consideration that depending on the sequencing resolution some insertional translocations may escape detection, these events are probably the rule rather than the exception (Slamova et al, ). This finding, beyond clarifying the mechanisms of readjustment of broken chromosomes, indicates that insertions should not be anymore considered simple three chromosome breakage events (Weckselblatt & Rudd, ), suggesting the opportunity to investigate the entire genome whenever a translocation insertion is evidenced, both if detected in the parent of a proband carrying an apparently de novo CNV or directly in the proband.…”
Section: Discussionmentioning
confidence: 99%
“…The breakpoints are usually consistent with canonical NHEJ [Kloosterman et al, 2011;Stephens et al, 2011;Marcozzi et al, 2018;Zepeda-Mendoza and Morton, 2019]. In addition, the pulverized DNA fragments may also be reassembled via alternative end-joining or via the co-occurrence of NHEJ and alternative end-joining [Kloosterman et al, 2012;Slamova et al, 2018]. Furthermore, chromothripsis induced by telomere crisis is often indicative of MMBIR [Cleal et al, 2019].…”
Section: Chromothripsismentioning
confidence: 99%